2022
DOI: 10.3390/molecules27113402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiome in Brain Development and Neurodegenerative Diseases

Abstract: Hundreds of billions of commensal microorganisms live in and on our bodies, most of which colonize the gut shortly after birth and stay there for the rest of our lives. In animal models, bidirectional communications between the central nervous system and gut microbiota (Gut–Brain Axis) have been extensively studied, and it is clear that changes in microbiota composition play a vital role in the pathogenesis of various neurodevelopmental and neurodegenerative disorders, such as Autism Spectrum Disorder, Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 199 publications
3
50
0
3
Order By: Relevance
“…Establishing the essentiality of NOB species for a healthy relationship between microbiota and their human/animal hosts will mark a new approach to the use of these species as prebiotic candidates in human and animal nutrition. The literature explains that the health of humans/animal organisms depends on the health of the microbiota [ 116 , 149 ], supporting the view that the role of NOB species is crucial for the health of the human/animal organism [ 34 ]. This role has resulted from many scientific experiments shown that NOB species increase the buffering capacity of saliva [ 77 , 81 ], have a positive impact on the intestinal and oral microbiome [ 76 ], protect important probiotic bacteria, namely Bifidobacterium spp.…”
Section: Perspectivesmentioning
confidence: 85%
See 1 more Smart Citation
“…Establishing the essentiality of NOB species for a healthy relationship between microbiota and their human/animal hosts will mark a new approach to the use of these species as prebiotic candidates in human and animal nutrition. The literature explains that the health of humans/animal organisms depends on the health of the microbiota [ 116 , 149 ], supporting the view that the role of NOB species is crucial for the health of the human/animal organism [ 34 ]. This role has resulted from many scientific experiments shown that NOB species increase the buffering capacity of saliva [ 77 , 81 ], have a positive impact on the intestinal and oral microbiome [ 76 ], protect important probiotic bacteria, namely Bifidobacterium spp.…”
Section: Perspectivesmentioning
confidence: 85%
“…In our opinion, in the future, B analysis from the feces and colonic mucus could become an important marker indicating the lack of B from nutrition and a predictive factor for several diseases resulting from unhealthy symbiosis. Subsequently, the commensal bacteria need B as an essential component of their diet for survival, thus proving B’s role in modulating microbiome physiology [ 116 ]. Furthermore, the male microbiome is different from the female one [ 117 ].…”
Section: Are Nob Species Essential For Healthy Human/animal Microbiom...mentioning
confidence: 99%
“…It is therefore crucial that constipation be considered an important modifying factor when analyzing gut bacteria composition. The question remains whether changes in gut microbiota are the cause or the consequence of altered peristaltic movements in PD subjects [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota–gut–brain axis has successfully linked the contents of the GM to various neurodegenerative disorders, developmental disorders, and mood changes [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The relationship between these diseases and the microbiota is mainly related to several bacterial metabolites that act as immunoregulatory and neurochemical factors [ 37 , 38 , 39 ].…”
Section: Microbiota–gut–brain Axis (Mgb)mentioning
confidence: 99%